Regulatory Dynamics of Sharia Securities in Indonesia’s Islamic Capital Market - Dena Ayu (Journal of Economicate Studies, 2022)
This study investigates the classification, governance, and institutional dynamics of Sharia securities within Indonesia’s Islamic capital market. Using a qualitative methodology grounded in document and thematic analysis, it explores how regulatory bodies—including the Financial Services Authority (OJK), the National Sharia Council (DSN-MUI), and the Indonesia Stock Exchange—coordinate to ensure Sharia compliance. Findings reveal that while regulatory instruments such as the Sharia Securities List (DES) and Jakarta Islamic Index have improved transparency and compliance, overlapping jurisdictions and limited enforcement mechanisms present notable challenges. Additionally, gaps in investor literacy and underdeveloped Sharia auditing hinder wider market participation. However, the market holds significant growth potential due to strong demographic demand, supportive government policy, and technological opportunities in fintech. The study offers theoretical and practical insights into strengthening institutional trust, regulatory harmonization, and ethical investing within Indonesia’s Islamic finance framework.